Ogień w filozofii Heraklita - Makowski, Piotr (Wydawnictwo Naukowe Instytutu Filozofii, 2012)
The author sketches the most important aspects of Heraclitean theory of fire as the ‘principle’, ‘beginning’ or ‘origin’ (arché) of existing things. The presentation puts his concept of arché in the background of Heraclitean famous aphoristic dicta (‘everything flows’ – panta rhei, among others) and his theory of universal logos. Although the philosophy of Heraclitus is not very distinct from other theories by archaic philosophers of nature (Anaximander, Anaximenes, Thales, Parmenides, Empedocles), its specificity makes Heraclitus one of the most influential and inspiring figures of Ancient world.
Fire in the Philosophy of Heraclitus
Keywords: Heraclitus; presocratics; arché; fire; logos